A review of proton therapy – Current status and future directions. Issue Volume 6:Issues 2(2022) (27th April 2022) - Mohan, Radhe
Abstract: The original rationale for proton therapy was its highly conformal depth‐dose distributions compared to photons, which allow greater sparing of normal tissues and escalation of tumor doses, thus potentially improving outcomes. Additionally, recent research has revealed previously unrecognized advantages of proton therapy. For instance, the higher relative biological effectiveness (RBE) near the end of the proton range can be exploited to increase the difference in biologically effective dose in tumors versus normal tissues. Moreover, the smaller "dose bath, " that is, the compact nature of proton dose distributions, has been found to reduce the exposure of circulating lymphocytes and the immune organs at risk. There is emerging evidence that the resulting sparing of the immune system has the potential to improve outcomes. Protons accelerated to energies ranging from 70 to 250 MeV enter the treatment head mounted typically on a rotating gantry. Initially, the beams of protons are narrow and, to be suitable for treatments, must be spread laterally and longitudinally and shaped appropriately. Such spreading and shaping may be accomplished electro‐mechanically for the "passively scattered proton therapy" (PSPT) mode; or it may be achieved through magnetic scanning of thin "beamlets" of protons. Intensities of scanning beamlets are optimized to deliver intensity‐modulated proton therapy (IMPT), which optimally balances tumor dose and the sparing of normal tissues. IMPT is presumably the most powerful form of proton therapy. The planning and evaluation of proton dose distributions require substantially different techniques compared to photon therapy. This is mainly due to the fact that proton dose distributions are highly sensitive to inter‐ and intra‐fractional variations in anatomy. In addition, for the same physical dose, the biological effectiveness of protons is different from photons. In the current practice of proton therapy, the RBE is simplistically assumed to have a constant value of 1.1. In reality, the RBE is variable and a highly complex function of numerous variables including energy of protons, dose per fraction, tissue and its environment, cell type, end point, and possibly other factors. While the theoretical potential of proton therapy is high, the clinical evidence in support of its use has so far been mixed. The uncertainties and assumptions mentioned above and the limitations of the still evolving technology of proton therapy may have diminished its true clinical potential. Although promising results have been reported for many types of cancers, they are often based on small studies. At the same time, there have been reports of unforeseen toxicities. Furthermore, because of the high cost of proton therapy, questions are often raised about its value. The general consensus is that there is a need for continued improvement in the state of the art of proton therapy. There is also a need to generate high level evidence of the potential of protons. Fortuitously, such efforts are taking place currently. Current research, aimed at enhancing the therapeutic potential of proton therapy, includes the determination and mitigation of the impact of the physical uncertainties on proton dose distributions through advanced image‐guidance and adaptive radiotherapy techniques. Since residual uncertainties will remain, robustness evaluation and robust optimization techniques are being developed to render dose distributions more resilient and to improve confidence in them. The ongoing research also includes improving our understanding of the biological and immunomodulatory effects of proton therapy. Such research and continuing technological advancements in planning and delivery methods are likely to help demonstrate the superiority of protons.